2007
DOI: 10.1002/art.23235
|View full text |Cite
|
Sign up to set email alerts
|

Uridine supplementation antagonizes zidovudine‐induced mitochondrial myopathy and hyperlactatemia in mice

Abstract: Objective. Zidovudine is an antiretroviral nucleoside analog reverse transcriptase inhibitor that induces mitochondrial myopathy by interfering with the replication of mitochondrial DNA (mtDNA). Because zidovudine inhibits thymidine kinases, the mechanism of mtDNA depletion may be related to an impairment of the de novo synthesis of pyrimidine nucleotides, which are required building blocks of mtDNA. This study was undertaken to determine whether mitochondrial myopathy is a class effect of antiretroviral nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Uridine supplementation during antiviral therapy has been shown to reduce peripheral neuropathy and encephalopathy in AIDS patients and in animal models, but the mechanism of this protective effect is not known (23,39). After uptake in cells, uridine can be metabolized to various nucleoside and nucleotide intermediates, e.g., uridine, cytidine, deoxycytidine, and thymidine nucleotides such as UTP, CTP, dCTP, and dTTP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uridine supplementation during antiviral therapy has been shown to reduce peripheral neuropathy and encephalopathy in AIDS patients and in animal models, but the mechanism of this protective effect is not known (23,39). After uptake in cells, uridine can be metabolized to various nucleoside and nucleotide intermediates, e.g., uridine, cytidine, deoxycytidine, and thymidine nucleotides such as UTP, CTP, dCTP, and dTTP.…”
Section: Discussionmentioning
confidence: 99%
“…dN, deoxynucleoside; dNMP, deoxynucleoside monophosphate; AZTMP, AZT monophosphate; AZTTP, AZT triphosphate; pol-␥, polymerase ␥. levels may explain in part the uridine effects observed in HIV patients and in animal models in connection with antiviral treatment with nucleoside analogs (23,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to defects in insulin secretion, decreased sensitivity in insulin target cells can also participate in diabetogenesis in patients receiving clevudine who might have a high susceptibility to mitochondrial toxicity. Interestingly, several reports have shown that NRTI induces intramitochondrial pyrimidine deficiency which may aggravate mtDNA depletion and mitochondrial dysfunction [35,36]. They also discovered that uridine supplementation attenuates steatohepatitis or mitochondrial myopathy induced by NRTI.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle capillaries are lost in dermatomyositis [1], systemic sclerosis [2-4], and chronic obstructive pulmonary disease (COPD) [5], and qualitative or quantitative defects of respiratory chain components are found in the mitochondrial myopathies [6,7]. Ultrastructural changes in mitochondria and respiratory-chain dysfunction can also be induced by medications (statins [8], zidovudine, and other antiretroviral nucleoside analogues [9], and potentially, alcohol [10]). The physiological explanations for muscle fatigue and the adjustments of muscle metabolism to such respiratory compromise have, however, been only poorly addressed.…”
Section: Introductionmentioning
confidence: 99%